Can tissue factor, a multifactorial molecule of the hemostasis, be used as a biomarker for thrombosis, inflammation and cancer? - Emekli, Nesrin (University of Istanbul, 2017)
Tissue factor (TF) is a transmembrane protein found in many tissues and is active in various biological reactions. It is a member of the cytokine receptor superfam-ily and is referred to as CD 142 because of this feature. TF is also known as Factor III in the coagulation system and binds FVII/VIIa. The TF and FVIIa complex has both procoagulant and signaling activities. It functions in many biological processes, including hemostasis, thrombosis, inflammation and cancer. TF is essential for haemostasis but increased TF expression within atherosclerotic plaques and TF positive microparticles were detected in thrombotic conditions. TF increases inflammation by enhancing intravascular fibrin deposition and activates protease-activated receptors (PARs). TF and FVIIa complex also contribute to tumor growth by activating PAR2. Recent retrospective studies have shown that TF positive microparticles increase in the plasma of cancer patients. Therefore TF may be suggested to be used as a biomarker. However further studies are required to reveal the availability of TF as a biomarker to identify cancer and risk of thromosis and inflammation.
Keywords: Cancer; Hemostasis; Inflammation; Thrombosis; Tissue Factor